1999
DOI: 10.1159/000026092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy and Toxicity of Treatment Using Rhenium-186 HEDP in Metastatic Bone Disease

Abstract: ABC 186 Re HEDP administered intravenously in the outpatient clinic. Methods: Patients were followed with pain diaries, records of medication, morbidity, sleep patterns, serial bone scans and a Karnofsky index. Twenty-five patients with complete records were evaluated. Patients were grouped according to the extent of bone metastases as seen in the bone scans. Results: Sixteen patients (64%) showed clinical responses of which 4 became completely painfree. Pain relief typically began 10-20 days after 186 Re HED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This finding could explain why a better response is seen in patients who have received higher doses (19)(20)(21). On the other hand, it might be a reasonable justification for a good response in patients with few metastatic lesions treated with a lower administered activity (22)(23)(24).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding could explain why a better response is seen in patients who have received higher doses (19)(20)(21). On the other hand, it might be a reasonable justification for a good response in patients with few metastatic lesions treated with a lower administered activity (22)(23)(24).…”
Section: Discussionmentioning
confidence: 95%
“…bone markers, hemoglobin level, and previous treatments (14,23,24,36), but highly controversial issues remain. Although several studies have demonstrated that earlier treatment in patients in better clinical condition may improve the response rate (22)(23)(24), unfortunately radionuclide therapy is underutilized in Iran. This underutilization could be a result of limited referrals due to specialists' inadequate knowledge and misconceptions about adverse effects or to the restricted availability and expense of bone painpalliating radionuclides.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lower doses may be enough to get a good response in patients with few metastatic lesions. [ 11 18 19 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…Possible side effects of this therapy can be significantly minimized upon careful selection of patients and administered dose. Although several studies have demonstrated that administering therapy, when the patient is in better clinical condition, may significantly improve the response rate,[ 18 19 31 ] this understanding has not been translated into a clinical practice to unleash the full potential of radionuclide therapy. This underutilization could be due to specialists' inadequate knowledge and misconceptions about the adverse effects of this mode of therapy or due to restricted availability and cost of bone pain-palliating radionuclides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation